2014
DOI: 10.1037/a0033663
|View full text |Cite
|
Sign up to set email alerts
|

Intensive reading remediation in grade 2 or 3: Are there effects a decade later?

Abstract: Despite data supporting the benefits of early reading interventions, there has been little evaluation of the long-term educational impact of these interventions, with most follow-up studies lasting less than two years (Suggate, 2010). This study evaluated reading outcomes more than a decade after the completion of an 8-month reading intervention using a randomized design with second and third graders selected on the basis of poor word-level skills (Blachman et al., 2004). Fifty-eight (84%) of the original 69 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 67 publications
(146 reference statements)
6
61
0
Order By: Relevance
“…In five instances the authors of original studies were contacted to clarify or obtain missing information (see Note 1). A further study (i.e., Blachman et al, 2014) reported, in addition to a 12-month follow-up, a 10-year follow-up; however, this was judged to be too great of an outlier with regard to follow-up to be included here, and instead the 12-month follow-up data are included. Only two studies had samples that had learning disabilities, so these were collapsed into the category of reading disabled, based on the reasoning that both represent severe learning impairment.…”
Section: Resultsmentioning
confidence: 99%
“…In five instances the authors of original studies were contacted to clarify or obtain missing information (see Note 1). A further study (i.e., Blachman et al, 2014) reported, in addition to a 12-month follow-up, a 10-year follow-up; however, this was judged to be too great of an outlier with regard to follow-up to be included here, and instead the 12-month follow-up data are included. Only two studies had samples that had learning disabilities, so these were collapsed into the category of reading disabled, based on the reasoning that both represent severe learning impairment.…”
Section: Resultsmentioning
confidence: 99%
“…Collectively, these findings have led to repeated calls for interventions to be delivered early in children’s school careers. Early interventions may be necessary in order to best help those children with or at risk of experiencing reading or mathematics difficulties (e.g., Blachman et al, 2014; Clark, Pritchard, & Woodward, 2010; Partanen & Siegel, 2014). …”
mentioning
confidence: 99%
“…These findings, which parallel the results of Al Otaiba et al (this issue), were interpreted as reflecting the need for a more sustained reading intervention and inadequate statistical power to detect small effects. However, we would suggest that in the context of other studies, the results of Blachman et al (2014) are meaningful.…”
mentioning
confidence: 76%
“…More important, what all three studies suggest is that for many students, 1 year of reading intervention is not sufficient. Like Blachman et al (2014), we wonder what the long-term effects would be for 2 years of sustained efforts for students not meeting grade-level benchmarks. Such sustained efforts make the most sense from a public health framework in which all students are screened, monitored, and receive increasingly intense interventions.…”
Section: Downloaded By [University Of Western Ontario] At 09:09 06 Fementioning
confidence: 99%
See 1 more Smart Citation